FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT HERNIA INGUINAL PADA LAKI-LAKI DI RUMAH SAKIT UMUM Dr. SOEDARSO PONTIANAK - Aisyah, Siti; Hernawan, Andri Dwi; Sutriswanto, Sutriswanto (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Inguinal hernia is originated from an organ protrusion, tissue or structur which is pass through of cavity, normally it is contain of pass through parts, internusinguinalism / laternalis annulus. For passing through of canalize inguinalis and out of abdomen cavity are pass through external inguinalis / medialis annulus. On a graph of inguinal hernia was be rise in soedarso hospital. On every years in dr. soedarso hospital was occur rising of inguinal hernia. As many as 24 cases were consist of 20 male and 4 female on 2011, on 2012 has increased become 90 cases. They were consist from 76 male and 14 female. And on 2013 on drsoedarso hospital was more increases become 107 cases, which is consist from 94 male and 13 female. The purpose of this research to know the incidence of inguinal hernia factors to outpatient clinic of general surgery dr.soedarso hospital of Pontianak.This research use case control design, the research sample of 88 respondents (44 cases and 44 control) are taken using accident sampling technique, using chi- square test by 95% confidence level.The result of research showed that there are many significant relationship between job (p. value = 0.000: or = 6.937,95 % ci = 2.440-19.716) constipation history (p. value= 0.049 : or =2,7 34,95% ci =0,985-7,585) chronic cough history (p. value 0.009 : or 3,659,95%  ci= 1,33-10,016 and physical activity (p. value = 0,033: or = 2,833 , 95%  ci = 1,066- 7,529), variable are related  15 obesity (p. value = 0,091). Suggested to the drsoedarsos hospital Pontianak for making a health promotion  clinic to healthy promotion activities it can use (take advantage) waiting room and space room hospital and also make a healthy campaign activities.Keywords: Inguinal Hernia, occupation, history of constipation, chronic cough, physical activity.